Rabbit model of Staphylococcus aureus implant-associated spinal infection - Oren Gordon; Robert J. Miller; John M. Thompson; Alvaro A. Ordonez; Mariah H. Klunk; Dustin A. Dikeman; Daniel P. Joyce; Camilo A. Ruiz-Bedoya; Lloyd S. Miller; Sanjay K. Jain (The Company of Biologists, 2020)
Post-surgical implant-associated spinal infection is a devastating complication commonly caused by Staphylococcus aureus. Biofilm formation is thought to reduce penetration of antibiotics and immune cells, contributing to chronic and difficult-to-treat infections. A rabbit model of a posterior-approach spinal surgery was created, in which bilateral titanium pedicle screws were interconnected by a plate at the level of lumbar vertebra L6 and inoculated with a methicillin-resistant S. aureus (MRSA) bioluminescent strain. In vivo whole-animal bioluminescence imaging (BLI) and ex vivo bacterial cultures demonstrated a peak in bacterial burden by day 14, when wound dehiscence occurred. Structures suggestive of biofilm, visualized by scanning electron microscopy, were evident up to 56 days following infection. Infection-induced inflammation and bone remodeling were also monitored using 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET) and computed tomography (CT). PET imaging signals were noted in the soft tissue and bone surrounding the implanted materials. CT imaging demonstrated marked bone remodeling and a decrease in dense bone at the infection sites. This rabbit model of implant-associated spinal infection provides a valuable preclinical in vivo approach to investigate the pathogenesis of implant-associated spinal infections and to evaluate novel therapeutics.